Assessment of pain syndrome in children of non-oncology palliative group - Olga Nahorna; Igor Grygus (Kazimierz Wielki University, 2020)
Annotation. In the process of rehabilitation examination, the assessment of pain in children of the palliative non-oncological group is a difficult task. This is due to a number of reasons: reduced communication skills, unclear pathogenesis, etiology, nature of pain. At the same time, identifying the pain syndrome and suppressing it will provide comfort to the child and confidence to the parents. The purpose of the study: analysis of pain syndrome in children who need palliative non-oncological care. Research methods: empirical methods (comparison, description, measurement), theoretical method (axiomatic), general logical methods (analysis, synthesis, generalization), pain intensity assessment scales. Research results. To assess the intensity of pain, the following were used: children's scale for pain assessment by facial expressions of Wong-Baker (1988) - 10 (21,3%) children, assessment of pain in children who cannot speak or with speech disorders (from 6 months to 7 years old) - FLACC scale - 10 (21,3%) children, visual analog scale (VAS) - 19 (40,4%), KUSS (1998) children's pain assessment scale - 8 (17,0%). The results of the assessment of pain intensity are interpreted in the ICF qualifier «b 280 feeling of pain». The results of the survey revealed the following indicators: b 280.4 absolute violations were found in 14 children, b 280.3 severe violations were recorded in 26 children, b 280.2 moderate violations were detected in 6 children, 280.1 mild violations in one child. At the same time, the survey showed that most often children express or complain about pain of various concentrations: in the muscles of the lower limbs - «Minor pain» - 4 (8,5%), «Mild pain» - 5 (10,6%), «Moderate pain» - 27 (57,4%), «Severe pain» - 8 (17,0%), «Excessive pain» - 3 (6,3%); in the muscles of the shoulder girdle: «Slight pain» - 12 (25,5%), «Mild pain» - 12 (25,5%), «Moderate pain» - 11 (23,4%), «Severe pain» - 9 (39,1%), «Excessive pain» - 3 (6,3%); in the back: «Minor pain» - 7 (15,8%), «Mild pain» - 13 (27,6%), «Moderate pain» - 11 (23,4%), «Severe pain» - 10 (21,2%), «Excessive pain» - 6 (12,7%); unexplained pain manifested by crying: «Slight pain» - 11 (23,4%), «Mild pain» - 17 (36,1%), «Moderate pain» - 9 (39,1%),« Severe pain» - 7 (14,8%), «Excessive pain" - 3 (6,3%). There were no children who did not have pain. Clarifying the localization of pain contributed to the idea that musculoskeletal problems caused by hypodynamia, long-term immobilization, forced pathological position of the body provoke a significant share of discomfort. Conclusion. Thus, there is a need to include pain assessment in the complex of rehabilitation examination of children with disabilities in order to form an integrated approach to the rehabilitation program.